2019
DOI: 10.3389/fmicb.2018.03240
|View full text |Cite
|
Sign up to set email alerts
|

Adult T-Cell Leukemia/Lymphoma-Related Ocular Manifestations: Analysis of the First Large-Scale Nationwide Survey

Abstract: Adult T-cell leukemia/lymphoma (ATL) is a rare and aggressive T-cell malignancy with a high mortality rate, resulting in a lack of information among ophthalmologists. Here, we investigated the state of ophthalmic medical care for ATL and ATL-related ocular manifestations by conducting the first large-scale nationwide survey in Japan. A total of 115 facilities were surveyed, including all university hospitals in Japan that were members of the Japanese Ophthalmological Society and regional core facilities that w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 37 publications
1
19
0
2
Order By: Relevance
“…Analyzing such reports, ocular infiltration of ATL was the most frequent manifestation, observed in almost all tissues in and around the eye, and with reports mainly arising from Japan (Goto et al, 1993;Shibata et al, 1997;Mori et al, 2003;Yoshikawa et al, 2005;Miyamura et al, 2009;Liu et al, 2010;Maruyama et al, 2013;Hirano et al, 2017;Shimono et al, 2017;Sabundayo et al, 2018;Yamada et al, 2019), followed by Martinique (Merle et al, 2005(Merle et al, , 2016Fares et al, 2018) and the United States (Liu et al, 2010;Larson et al, 2012). In 2018, our nationwide survey in Japan confirmed that the most frequent ATL-related ocular manifestation was ATL infiltration (Kamoi et al, 2018).…”
Section: Atl and Ocular Diseasesupporting
confidence: 60%
See 3 more Smart Citations
“…Analyzing such reports, ocular infiltration of ATL was the most frequent manifestation, observed in almost all tissues in and around the eye, and with reports mainly arising from Japan (Goto et al, 1993;Shibata et al, 1997;Mori et al, 2003;Yoshikawa et al, 2005;Miyamura et al, 2009;Liu et al, 2010;Maruyama et al, 2013;Hirano et al, 2017;Shimono et al, 2017;Sabundayo et al, 2018;Yamada et al, 2019), followed by Martinique (Merle et al, 2005(Merle et al, , 2016Fares et al, 2018) and the United States (Liu et al, 2010;Larson et al, 2012). In 2018, our nationwide survey in Japan confirmed that the most frequent ATL-related ocular manifestation was ATL infiltration (Kamoi et al, 2018).…”
Section: Atl and Ocular Diseasesupporting
confidence: 60%
“…However, all manifestations have been reported as case reports or case series because of the rarity of cases and the difficulty of documentation resulting from the severe condition and high fatality rate of patients. In the late 2010s, we performed a nationwide survey and identified the frequency of ATL-related ocular manifestations (Kamoi et al, 2018).…”
Section: History Of Htlv-1-associated Ocular Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…HTLV integrates the transcribed RNA as a DNA provirus into the cell nucleic acid [12][13][14][15][16], and this simple evolutionary procedure leads to the persistence of the virus and its maintenance in nature and has serious implications for the different clinical and epidemiological outcomes of the infection and diseases associated with the virus. The wide array of clinical outcomes shows the target complexity within the human host (including the CNS, blood, lungs, eyes, muscles, bladder and skin), and several medical specialties have to be involved in the care and treatment of infected and diseased persons [17][18][19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%